Lo silente desde el proceso creativo - Nabón Hernández, Sebastián Andrés (2023)
This work aims to investigate through a compositional process how the notion of silence/the silent can be transposed in different ways, in different temporal and structural scales of the compositional process, and how this concept can condition the choice, exclusion, and treatment of materials and can give answers in terms of time, structure and form. It intends to go beyond the explicit notation of silence or its use as an articulator of a piece's temporal/formal structure. This memorial seeks to contribute to the construction and transformation of our subjectivities, our listeners, and the implications that our proposals have for the rest of society. Our political, social, and psychological implications, to name a few, are in dialogue with our sound discourses. As an active part of the dialogue, we must listen and then say. Moreover, in order to listen, we must be silent.